The Role of Egg Yolk in Modulating the Virulence of Salmonella Enterica Serovar Enteritidis - Xu, Yumin; Abdelhamid, Ahmed G.; Sabag-Daigle, Anice; Sovic, Michael G.; Ahmer, Brian M.M.; Yousef, Ahmed E. (Frontiers in Cellular and Infection Microbiology, 2022)
Contribution of food vehicles to pathogenicity of disease-causing microorganisms is an important but overlooked research field. The current study was initiated to reveal the relationship between virulence of Salmonella enterica serovar Enteritidis and egg yolk as a hosting medium. Mice were orally challenged with Salmonella Enteritidis cultured in egg yolk or tryptic soy broth (TSB). Additionally, mice were challenged with Salmonella Enteritidis cultured in TSB, followed by administration of sterile egg yolk, to discern the difference between pre-growth of the pathogen and its mere presence in egg yolk during infection. The pathogen’s Lethal dose 50 (LD50) was the lowest when grown in yolk (2.8×10^2 CFU), compared to 1.1×10^3 CFU in TSB, and 4.6×10^3 CFU in TSB followed by administration of sterile yolk. Additionally, mice orally received Salmonella Enteritidis grown in egg yolk expressed high death rate. These findings were supported by transcriptional analysis results. Expression of promoters of virulence-related genes (sopB and sseA) in genetically modified Salmonella Enteritidis reporter strains, was significantly higher (p < 0.05) when the bacterium was grown in the yolk, compared to that grown in TSB. Sequencing of RNA (RNA-seq) revealed 204 differentially transcribed genes in Salmonella Enteritidis grown in yolk vs. TSB. Yolk-grown Salmonella Enteritidis exhibited upregulated virulence pathways, including type III secretion systems, epithelial cell invasion, and infection processes; these observations were confirmed by RT-qPCR results. The transcriptomic analysis suggested that upregulation of virulence machinery of Salmonella Enteritidis grown in egg yolk was related to increased iron-uptake, biotin utilization, flagellar biosynthesis, and export of virulence proteins encoded on Salmonella pathogenicity island 1, 2, 4, and 5. These biological responses may have acted in concert to increase the virulence of Salmonella infection in mice. In conclusion, growth in egg yolk enhanced Salmonella Enteritidis virulence, indicating the significance of this food vehicle to the risk assessment of salmonellosis.